Compare use of subcutaneous drain vs. no drain in obese women to reduce wound complications post caesarean section: a randomized control trial - Asokan, Rosan; Sirsam, Shyam Kumar; Koranne, Prachi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Wound complications such as infection, seroma and dehiscence are more common in obese women after caesarean section. The use of subcutaneous drains has been proposed to minimize postoperative complication. This study aimed to evaluate the effectiveness of subcutaneous drains in reducing wound complications among obese women undergoing caesarean section. Methods: A randomized controlled trial was conducted at Government Medical College, Akola, over 18 months. A total of 150 obese women undergoing caesarean section were randomized into two groups: Group A (with subcutaneous drain) and Group B (without drain). Both groups were comparable in age, parity, BMI and haemoglobin levels. Postoperative complications were assessed, along with duration of hospital stay and time to suture removal. Results: Women without drains experienced significantly higher wound complications: superficial infection (17.5% vs 7.14%, p<0.05), deep infection (12.5% vs 4.29%, p<0.05) and seroma formation (27.5% vs 7.14%, p<0.001). Wound gape (20% vs 10%) and postoperative fever (15% vs 5.71%) were also more common in the no-drain group. Mean hospital stay and suture removal time were significantly shorter in the drain group (p<0.001). Conclusions: Subcutaneous drain placement after caesarean section in obese women significantly reduces wound infection, seroma formation and postoperative morbidity, leading to faster recovery and shorter hospital stays. Routine use of drains may be beneficial in this high-risk population.